2020
DOI: 10.1136/bmjresp-2020-000770
|View full text |Cite
|
Sign up to set email alerts
|

Physiological tests of small airways function in diagnosing asthma: a systematic review

Abstract: BackgroundAsthma is a common, heterogeneous disease that is characterised by chronic airway inflammation and variable expiratory airflow limitation. Current guidelines use spirometric measures for asthma assessment. This systematic review aimed to assess whether the most commonly reported tests of small airways function could contribute to the diagnosis of asthma.MethodsStandard systematic review methodology was used, and a range of electronic databases was searched (Embase, MEDLINE, CINAHL, CENTRAL, Web of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Nonetheless, in asthmatic patients with normal FEV 1 , MMEF has been reported below normal values, indicating small airways dysfunction as part of the disease paradigm. 22 The usefulness of BDR in managing COPD patients is also unclear. Even in the absence of FEV 1 improvement, Vital Capacity and Inspiratory Capacity can increase following inhaled bronchodilator use and these improvements are reflected in reduced dyspnea and increased exercise performance.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in asthmatic patients with normal FEV 1 , MMEF has been reported below normal values, indicating small airways dysfunction as part of the disease paradigm. 22 The usefulness of BDR in managing COPD patients is also unclear. Even in the absence of FEV 1 improvement, Vital Capacity and Inspiratory Capacity can increase following inhaled bronchodilator use and these improvements are reflected in reduced dyspnea and increased exercise performance.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, there are some clinical research works on these differences. Kobayashi et al [31] compared CANO (2CM) and CANO (TMAD) in patients with untreated asthma and showed that maximal mid-expiratory flow, which may be related to airway obstruction in peripheral airways [32], was correlated with both CANO (2CM) and CANO (TMAD) ; however, FEV 1 /FVC and sputum eosinophils were correlated with CANO (2CM) , but not with CANO (TMAD) [31]. Similarly, Sato et al [33] reported that CANO (2CM) , but not CANO (TMAD) , was negatively correlated with % predicted FEV 1 in patients with steroid-naïve asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The MMEF has been used to help exclude cough variant asthma from chronic cough of other causes 62 and has been found to be abnormal in patients with mild asthma and bronchodilator reversibility. 39 Compared to the FEV 1 , the percentage predicted of MMEF has consistently been lower in multiple groups with asthma, despite a normal or near-normal percentage predicted FEV 1 63 . Nevertheless, high variability and poor reproducibly are the major drawbacks of using MMEF in diagnosis.…”
Section: The Diagnostic Challenge Of Asthma; Can Tests Of Small Airways Help?mentioning
confidence: 94%